Perlindungan Konsumen dan Kualitas Pelayanan Transportasi Online di Kota Tangerang Selatan - Pendi Ahmad; Bima Guntara; Dadang Dadang (Wajah Hukum, 2021)
The development of the times and the rapid pace of globalization that is getting faster make humans need adequate transportation facilities so that a technology in the field of online-based transportation has developed using an application via a smartphone. Based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number 118 of 2018 concerning the Administration of Rental Vehicles and Regulation of the Minister of Transportation Number 12 of 2019 concerning Safety Protection of Motorbike Users Used in the Interest of the Community, online transportation is now a new and alternative breakthrough in fulfilling the needs of the public. do not have private vehicles as happened to the community in South Tangerang City. However, the presence of online transportation in the community forgets something that is so important, namely its protection as a consumer. This study aims to determine consumer protection for users of online transportation services in South Tangerang City according to Law Number 8 of 1999 concerning Consumer Protection and to determine the quality of online transportation services in South Tangerang City. The research method uses qualitative methods using an empirical juridical approach. Data samples were taken from key informants such as PT. Karya Anak Bangsa (Go-Jek) Application, PT. Indonesian Transportation Solutions (Grab), online transportation drivers, and of course the people of South Tangerang City who are directly involved in the implementation of consumer protection and service activities on online transportation in South Tangerang City. Meanwhile, the supporting informants in this study were the South Tangerang City Police and the South Tangerang City Transportation Agency as government agencies that indirectly knew about consumer protection and the quality of online transportation services in South Tangerang City. The results of the study found that consumer protection for online transportation users in South Tangerang City was quite good, this can be seen from the results of interviews with online transportation service providers such as Gojek and Grab that have implemented SOPs (Standard Operational Procedures) when consumers experience losses both formal and material and also There are no reports from the public to the South Tangerang Police who feel aggrieved as a consumer of online transportation. In addition, the quality of online transportation services in South Tangerang City is quite good, but there are still some consumer complaints such as the driver asking to be canceled, the driver canceling unilaterally, the driver coming too long to pick up, the driver using a different vehicle, and the time to arrive at a different destination. longer than the estimated time in the application.